Respuesta :

6h - (9 - 3h) = 6 - 3(h + 2)

First, distribute -1 to 9 and -3h and -3 to h and 2

-1(9 - 3h) = -9 + 3h

-3(h + 2) = -3h - 6

6h - 9 + 3h = 6 - 3h - 6

Simplify. Combine like terms

9h - 9 = -3h

Isolate the h. Subtract 9h from both sides

9h (-9h) - 9 = -3h (-9h)

-9 = -12h

Divide -12 from both sides

-9/-12 = -12h/-12

h = -9/-12

h = 3/4

B. one is your answer, and the solution is 3/4

hope this helps

The answer is B. One solution

I attached the work for this problem, and if you have any further questions feel free to ask.

Hope this helps.

Ver imagen xXPeachXx